1958
DOI: 10.1111/j.1748-1716.1958.tb01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Direct Stimulation of the Carotid Sinus Nerve in Man.

Abstract: The reflex haro-and chenioreceptor control of the cardiovascular system has for many years moused considerable interest, especially since it has recently been shown that the activity of the carotid baroreceptors is not only dependent on the distension of the sinus region by the blood pressure. The activity of a t least one type of the receptors is also markedly affected by local changes in intramural tension, caused by the smooth inuscle cells. Thus, local applications of vasocoiistrictor drugs induce a consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
7

Year Published

1969
1969
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 10 publications
4
42
0
7
Order By: Relevance
“…It is well known that changes in peripheral vascular resistance occur as a result of reflexes mediated by the baroreceptor system (1)(2)(3)(4)(5)(6)(7)(8)(9). Since a considerable proportion of the total cardiac output is directed through blood vessels supplying skeletal muscle and skin (10), the resistance vessels in these tissues could play an important role in the regulation of arterial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that changes in peripheral vascular resistance occur as a result of reflexes mediated by the baroreceptor system (1)(2)(3)(4)(5)(6)(7)(8)(9). Since a considerable proportion of the total cardiac output is directed through blood vessels supplying skeletal muscle and skin (10), the resistance vessels in these tissues could play an important role in the regulation of arterial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In a study published in 1958 Carlsten et al examined humans undergoing neck/head surgery and confirmed that carotid stimulation did reduce blood pressure in a frequency-dependent manner [35].…”
Section: History Of Baroreceptor Investigationmentioning
confidence: 92%
“…Первой демонстрацией эффекта стимуляции барорефлекса на человеке в 1958г была работа Carlsten et al [29]. В ней изучали больныx с опухо-лями шеи, у которых имелась необходимость хирур-гических манипуляций в области каротидного Всего за короткий период было опубликовано 64 случая применения электрической активации барореф-лекса [32][33][34].…”
Section: инновационные методы лечения резистентной агunclassified
“…Первой демонстрацией эффекта стимуляции барорефлекса на человеке в 1958г была работа Carlsten et al [29]. В ней изучали больныx с опухо-лями шеи, у которых имелась необходимость хирур-гических манипуляций в области каротидного К 50-ЛЕТИЮ РОССИЙСКОГО КАРДИОЛОГИЧЕСКОГО ОБЩЕСТВА синуса.…”
Section: инновационные методы лечения резистентной агunclassified
See 1 more Smart Citation